Demonstration of acoustic vibration sensor based on microfiber knot resonator. Issue 5 (23rd March 2013) - Sulaiman, A.; Muhammad, M. Z.; Harun, S. W.; Arof, H.; Ahmad, H.
Abstract A compact microfiber‐based acoustic vibration sensor is demonstrated using microfiber knot resonator (MKR) structure, which is fabricated by flame brushing technique. It is observed that the extinction ratio of the resonant spectrum of the knot resonator is linearly proportional to the vibration amplitude. This is attributed to the interruption of the effective coupling of the MKR which is correlated with the exposed vibration force. It is also shown that the resonant wavelength shifts by about 0.19 nm as the normalized vibration energy is increased from 0 to 10%. The performance of the sensor is then further investigated by monitoring the fast Fourier transform (FFT) of the signal when the MKR is exposed to various vibration frequencies as a narrowband 1545 nm laser is injected into the MKR. In the spectra of the signals, the frequency of the applied vibration is clearly shown as it has the highest magnitude followed by the accompanying harmonics. This holds true for all vibration frequencies. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:1138–1141, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27526